ANALISIS EFEKTIVITAS DAN KONTRIBUSI BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN TERHADAP PAJAK DAERAH PADA BADAN PENGELOLA PAJAK DAN RETRIBUSI DAERAH KABUPATEN MINAHASA - Koagouw, Brenda; Karamoy, Herman; Lambey, Robert (Universitas Sam Ratulangi, 2018)
Local tax is one of the income source which came from every region and can be improve depends on the situation of every region and they have extensive rights to excavating, managing, and using all the natural resources also another potential which can be found in its region. The income which came from local tax from time to time must be increased because if the income of local tax revenue increase, then the income of tax revenue in its region also increase as well. One of the most potential local tax income is duties on acquiring land and building rights. The purpose of this research is to find out about the effectiveness and the contribution of duties on acquiring land and building rights in Minahasa Regency. The analysis method used in this research is descriptive with quantitative approach. The result of this research found out that the effectiveness of duties on acquiring land and building rights in 2013-2017 is in the criteria of â€œvery goodâ€ while the contribution of duties on acquiring land and building rights to local tax at 2013-2016 still in the criteria of â€œnot goodâ€ but in the year of 2017 the contribution has improved and is in the criteria of â€œpretty goodâ€. Keywords : Effectiveness, Contribution, Tax Income, Duties On Acquiring Land And Building Rights, Local Tax